2022
DOI: 10.1039/d1fo03386g
|View full text |Cite
|
Sign up to set email alerts
|

A review on selenium-enriched proteins: preparation, purification, identification, bioavailability, bioactivities and application

Abstract: Selenium (Se) deficiency can cause many diseases and then affect human health. Traditional inorganic Se supplements have disadvantages of toxicity and low bioavailability. Se-enriched proteins have good bio-accessibility and high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Moreover, the growth-promoting response to foliar application of selenium was demonstrated in some leafy crops, including chicory (Germ et al 2007), cilantro (Kopsell et al, 2009), pak choi (Li et al, 2015), celery (Li et al, 2020), and cabbage (Yang et al, 2022, Antoshkina et al, 2023, Yu et al, 2023. Also, the increases in nutrient contents obtained in the current study are in harmony with the previous studies for many crops (Wen et al, 2022). Furthermore, the current study demonstrated that foliar application of selenium at 30 μM significantly raised the selenium concentration in the leaves by 69 and 39% in the first and second seasons, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the growth-promoting response to foliar application of selenium was demonstrated in some leafy crops, including chicory (Germ et al 2007), cilantro (Kopsell et al, 2009), pak choi (Li et al, 2015), celery (Li et al, 2020), and cabbage (Yang et al, 2022, Antoshkina et al, 2023, Yu et al, 2023. Also, the increases in nutrient contents obtained in the current study are in harmony with the previous studies for many crops (Wen et al, 2022). Furthermore, the current study demonstrated that foliar application of selenium at 30 μM significantly raised the selenium concentration in the leaves by 69 and 39% in the first and second seasons, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Two reviews have appeared this year on Se speciation focused on different applications. The preparation, purification, bioactivities, and application of Se-enriched proteins have been extensively reviewed by Wen et al 104 The paper is divided into several sections: (1) preparation and purification of Se-enriched proteins obtained from different resources (microorganisms, plants, and animals). In this section the performance of different methods of extracting Se-proteins are critically evaluated such as nature of the solvents (water, salt, ethanol, alkali solution extraction) and extraction techniques (ultrasound assisted and pulsed electric field assisted extraction); (2) bioactivity of Se-enriched proteins and their hydrolysates.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…Ch. Wen et al [98] note that conventional inorganic Se supplements have drawbacks such as toxicity and low bioavailability. Enriched Se proteins and their hydrolysates show good bioactive properties, mainly including antioxidant activity, immune regulation, neuroprotective activity and inhibition of hyperglycaemia, among others.…”
Section: Preliminary Research Towards Selenium-enriched Protein -Natu...mentioning
confidence: 99%